2018
DOI: 10.1177/1078155218801066
|View full text |Cite
|
Sign up to set email alerts
|

Laxative co-medication and changes in defecation patterns during opioid use

Abstract: Introduction Opioid-induced constipation is a clinically relevant side effect and a cause of potentially avoidable drug-related hospital admissions. Objectives To describe the presence of laxative co-medication, the reasons for not starting laxatives and to evaluate changes in stool patterns of opioid initiators. Methods In this observational study community pharmacists evaluated the availability of laxative co-medication in starting opioid users and registered reasons for non-use. Two opioid initiators per ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The level of adherence in this study is in line with or slightly higher than in older studies both in the Netherlands [ 14 , 15 ] and outside [ 17 19 ], while more recent studies tend to show higher levels of adherence [ 16 , 20 ] However, while these studies only looked at overall adherence, we investigated practice variation. Since the upper level of the range of adherence is 88%, an increase in the overall level of adherence seems achievable.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The level of adherence in this study is in line with or slightly higher than in older studies both in the Netherlands [ 14 , 15 ] and outside [ 17 19 ], while more recent studies tend to show higher levels of adherence [ 16 , 20 ] However, while these studies only looked at overall adherence, we investigated practice variation. Since the upper level of the range of adherence is 88%, an increase in the overall level of adherence seems achievable.…”
Section: Discussionsupporting
confidence: 86%
“…Especially since OIC carries a risk of hospitalisation [ 31 ]. The study by De Bruin et al [ 16 ] confirmed that patients are not always convinced they need laxatives when using opioids, further stressing the need for patient information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An observational study conducted in the Netherland identified that OIC was a major reason of unplanned hospital admissions, which is a preventable side effect. 5 Considering the situation of Pakistan where the availability hospital beds is quite challenging, and the patients access to treatment is also difficult. The physician should co-prescribe any form of laxative along with opioids.…”
Section: Discussionmentioning
confidence: 99%